2010
DOI: 10.4065/mcp.2009.0620
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Coronary Artery Calcium Assessment for Evaluating Chest Pain in the Emergency Department: Long-term Outcome of a Prospective Blind Study

Abstract: For editorial comment, see page 309 C hest pain is the presenting concern for more than 8 million emergency department (ED) visits annually. The ED evaluation of chest pain is resource-intense and has inherent limitations. Medical history and physical examination frequently yield little insight into the source of the chest pain. More than one-third of patients with docu- OBJECTIVE: To determine the long-term outcome of computed tomographic (CT) quantification of coronary artery calcium (CAC) used as a triage t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 59 publications
3
20
0
Order By: Relevance
“…The ability of calcium imaging to rule out ACS in low-risk patients has been demonstrated repeatedly, and a negative calcium score is associated with an excellent prognosis. [13][14][15][16][17] The combined data in this study similarly demonstrate the high negative predictive value of a negative calcium scan. There was a single myocardial infarction in ≈800 patients with a negative calcium scan, whereas another 3 patients were classified as unstable angina.…”
Section: Niemansupporting
confidence: 61%
“…The ability of calcium imaging to rule out ACS in low-risk patients has been demonstrated repeatedly, and a negative calcium score is associated with an excellent prognosis. [13][14][15][16][17] The combined data in this study similarly demonstrate the high negative predictive value of a negative calcium scan. There was a single myocardial infarction in ≈800 patients with a negative calcium scan, whereas another 3 patients were classified as unstable angina.…”
Section: Niemansupporting
confidence: 61%
“…[138][139][140][141][142][143][144][145][146][147][148][149][150] We also identified a prognostic study of CT CAC scoring without angiography. 151 Two of the prognostic studies of CTCA reported different follow-up for the same cohort, 132,133 and two of the prognostic studies of exercise ECG reported some patients in common. 138,140 The lack of any diagnostic studies comparing exercise ECG with ICA is not surprising, as exercise ECG only started to be used in patients presenting to hospital with acute pain many years after its diagnostic accuracy for CAD had been evaluated in patients with stable chest pain.…”
Section: Studies Included In the Computed Tomographic Coronary Angiogmentioning
confidence: 99%
“…The study of CT CAC scoring 151 reported that 9 out of 91 patients with a CAC score of > 0 had MACEs (two MI and nine PCI), compared with 0 out of 82 with a CAC score = 0.…”
Section: Q4 Is a Mace Identification And Definition Independent Of Thmentioning
confidence: 99%
“…CACS may also challenge SPECT, which requires additional patient preparation, must be performed in conjunction with a stressor modality through coordination of medical and technical staff, is dependent on radiotracer availability, has higher radiation exposure, and may require considerable expertise for accurate interpretation. Most low-to-intermediaterisk patients (;55%) with ACP have a CACS of 0 (7,17,(23)(24)(25)(26)(27)(28) in whom there is a low likelihood of abnormal SPECT (0.8%) (7) or significant CAD as shown in the current study. Pooled data from 8 studies and ours suggest high sensitivity (96%; 95% confidence interval, 92%-98%) and negative predictive accuracy (99.4%; 95% confidence interval, 99%-100%) (7,17,(23)(24)(25)(26)(27)(28) for excluding ACS with CACS, which is comparable to CTA or SPECT (3)(4)(5)(6)(7)9).…”
Section: Cacsmentioning
confidence: 86%